The interplay of contextual elements in implementation: an ethnographic case study - McCullough, Megan B (BMC Health Serv Res, 2015)
BACKGROUND: Contextual elements have significant impact on uptake of health care innovations. While existing conceptual frameworks in implementation science suggest contextual elements interact with each other, little research has described how this might look in practice. To bridge this gap, this study identifies the interconnected patterns among contextual elements that influence uptake of an anticoagulation clinic improvement initiative. METHODS: We completed 51 semi-structured interviews and ethnographic observations across five case study sites involved in an evidence-based practice (EBP) quality improvement initiative. We analyzed data in NVivo 10 using an a priori approach based on the Promoting Action on Research Implementation in Health Services (PARIHS) model and an emergent thematic analysis. RESULTS: Key contextual elements, such as leadership, teamwork, and communication, interacted with each other in contributing to site-level uptake of the EBP, often yielding results that could not be predicted by looking at just one of these elements alone. Sites with context conducive to change in these areas predictably had high uptake, while sites with uniformly weak contextual elements had low uptake. Most sites presented a mixed picture, with contextual elements being strongly supportive of change in some areas and weak or moderate in others. In some cases, we found that sites with strong context in at least one area only needed to have adequate context in other areas to yield high uptake. At other sites, weak context in just one area had the potential to contribute to low uptake, despite countervailing strengths. Even a site with positive views of EBPs could not succeed when context was weak. CONCLUSION: Interrelationships among different contextual elements can act as barriers to uptake at some sites and as facilitators at others. Accounting for interconnections among elements enables PARIHS to more fully describe the determinants of successful implementation as they operate in real-world settings.